Education, Pedagogy and Andragogy - Eripuddin; Jufrizal (JEE (Journal of English Education), 2021)
This article discusses the basic concept and theories of education, pedagogy and andragogy. It explores various scholarly definitions and consepts about tranferring the knowledge to young learners and adult learners. The article will be useful for practicing teachers, students, college and university lecturers, school-based in-service coordinators, advisory teachers and school mentors dealing with the concepts and theories of education, pedagogy, and andragogy. This is a theoretical-based on the literature study. The result of the study argues that the competencies in teaching and understanding students in learning whether young learners and adult learners are an appropriate system in education. So, educators or stakeholders should consider for more understanding about education, pedagogy and andragogy in technology era now. The success of an education is largely determined by the approach used by educators and teachers in understanding concepts of education, pedagogy and andragogy, and learning material as well.